IN VITRO AND IN SILICO ALPHA-AMYLASE INHIBITION POTENTIAL (ANTI-DIABETIC ACTIVITY) OF PSEUDERANTHEMUM BICOLOR (SIMS) RADIK - BS, RAMESH; RAVI, LOKESH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Aim of this study is to evaluate theanti-diabetic activity of Pseuderanthemum bicolor commonly called limang-sugat by inhibiting alpha-amylase protein. Methods: Leaves of P. bicolor were extracted with methanol, chloroform, and ethyl acetate. The extracts were subjected for alpha-amylase inhibition assay and gas chromatography–mass spectrometry (GC–MS) analysis. Phytochemical compounds identified by GC-MS were subjected for protein-ligand docking study against alpha-amylase protein. Acarbose was used as a positive standard drug. Results: The major bioactive compounds obtained from methanol, chloroform, and ethyl acetate extracts were 1,6;2,3-Dianhydro-4-Deoxy-Beta-D-Ribo-Hexopyranose, Pseduosarsasapogenin-5,20-Dien, methyl ether/Hexatriacontane, Di-N-decylsulfone/Octadecanal, and squalene, respectively. A total of 19 secondary metabolites were subjected for protein–ligand docking study against the alpha-amylase protein. The reference drug acarbose demonstrated binding energy of −7.8 Kcal/mol and formed 20 hydrogen bonds with the enzyme. Acarbose signified high polar interaction with the amylase enzyme. Among the 19 test ligands, “2,2-Dibromocholestanone” from ethyl acetate extract exemplified the highest binding energy of −9.3 Kcal/mol. The next highest remarkable inhibition was showed by “Pseduosarsasapogenin-5,20-Dien Methyl Ether” present in the methanol extract, with a binding energy of -9.3 Kcal/mol with the formation of 2 hydrogen bonds. Conclusion: From the result, it could be concluded that the P. bicolor leaves contain various bioactive compounds which are considered as a good anti-diabetic drug.